Lepteridine as a unique fluorescent marker for the authentication of manuka honey. (15th June 2017) - Lin, Bin; Loomes, Kerry M.; Prijic, Gordana; Schlothauer, Ralf; Stephens, Jonathan M.
Highlights: Lepteridine is responsible for MM2 fluorescence in manuka honey. Lepteridine is derived from Leptospermum scoparium nectar. Lepteridine is present in the wider Australian Leptospermum genus. In New Zealand, lepteridine is not present in other honeys. Abstract: The recent discovery of two unique manuka marker fluorescence wavelengths (MM1 and MM2) potentially offers a rapid and cost-effective approach for manuka honey authentication using spectroscopy. The fluorophore responsible for the MM1 marker has been identified as leptosperin. We investigated whether lepteridine may be responsible for the MM2 fluorescence. We quantified the lepteridine in manuka honey and manuka nectar, which ranged between 5–52 mg/kg and 80–205 mg/kg, respectively. Notably, the fluorescent spectrum of synthetic lepteridine matched the MM2 fluorescence signature. Fluorescence quenching was observed in the honey matrix but otherwise, lepteridine was stable over prolonged storage at 37 °C. Lepteridine was also found in Australian Leptospermum honeys and nectars. Lepteridine concentration was positively correlated with concentrations of the MM1 fluorescence marker leptosperin in honeys. These findings identify lepteridine as the principle compound responsible for MM2 fluorescence, and support the utility as a marker compound for manuka honey authentication.